2010
DOI: 10.1007/s11104-010-0454-7
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of rice production using endophytic strains of Rhizobium leguminosarum bv. trifolii in extensive field inoculation trials within the Egypt Nile delta

Abstract: This study assessed the ability of biofertilizer inoculants containing Rhizobium leguminosarum bv. trifolii to enhance production of rice (Oryza sativa L.) under actual agricultural conditions in the Nile delta. Large-scale field experiments evaluated 5 rice varieties inoculated with 7 endophytic rhizobial strains during 5 growing seasons, including at sites ranked as the world's highest in rice production. Inoculation with single strains or multi-strain consortia significantly increased grain yield in 19 of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
35
0
6

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(46 citation statements)
references
References 30 publications
5
35
0
6
Order By: Relevance
“…Autor para correspondência. II (PERRINE-WALKER et al, 2007;YANNI & DAZZO, 2010;OSORIO FILHO et al, 2014;HAHN et al, 2014). Vivendo endofiticamente, os rizóbios podem estimular o crescimento das plantas, devido à produção de substâncias hormonais, principalmente auxinas (BISWAS et al, 2000), a solubilização de fosfatos (RODRIGUEZ & FRAGA, 1999) e a proteção das plantas contra patógenos (MISHRA et al, 2006).…”
Section: Introductionunclassified
See 1 more Smart Citation
“…Autor para correspondência. II (PERRINE-WALKER et al, 2007;YANNI & DAZZO, 2010;OSORIO FILHO et al, 2014;HAHN et al, 2014). Vivendo endofiticamente, os rizóbios podem estimular o crescimento das plantas, devido à produção de substâncias hormonais, principalmente auxinas (BISWAS et al, 2000), a solubilização de fosfatos (RODRIGUEZ & FRAGA, 1999) e a proteção das plantas contra patógenos (MISHRA et al, 2006).…”
Section: Introductionunclassified
“…Do sistema radicular, essas bactérias ascendem pelo xilema para a parte aérea (YANNI & DAZZO, 2010). Em arroz, os rizóbios podem acelerar a germinação das sementes, estimular o crescimento radicial, melhorar a absorção de nutrientes, estimular o crescimento da parte aérea e aumentar o rendimento de grãos (BISWAS et al, 2000;YANNI et al, 2001).…”
Section: Introductionunclassified
“…The finding that Rhizobia can also form endophytic associations with rice and are able to colonize all the internal tissues of plant suggests that such interactions can have a major role in plant fitness and productivity. Surprisingly, the interactions proved to be strain and variety specific [2] indicating that the growth responses are indeed heritable traits. Large-scale field trials evaluating five rice varieties and seven Rhizobia strains over five seasons showed that bacterial treatments increased yield by up to 47% in farmers' fields, with an average increase of 19.5%.…”
Section: Introductionmentioning
confidence: 97%
“…Other possible benefits of the succession of legume/grass crop system are the production of phytohormones and other plant stimulating substances by rhizobia symbionts with the species that inhabit the rhizosphere of crops that follow them (Yanni and Dazzo, 2010;Yanni et al, 2011).…”
Section: Introductionmentioning
confidence: 99%